Diseño de un folleto fotográfico e ilustrado basado en la diagramación editorial, acerca de la historia, vida y tradiciones de los chagras del cantón Mejía, provincia de Pichincha, como medio de promoción turística, en el período 2015 - Caiza Guanochanga, Paúl Fernando (2016)
The goal research is to promote new forms of communication such as the use of an illustrated and photo booklet based on graphic production editorial, about life, history and traditions of Mejia Canton’s Chagras, Pichincha Province, as a means of tourism promotion. One of the greatest realities that holds our society is the true cultural identity’s loss, as customs and traditions, which unfortunately every day are in decline, with other cultures that are imposed on our origins. It is why we should form basis for new generations to integrate humanity with knowledge that lead the cultural identity formation….